Pengaruh Subtitusi Tepung Labu Kuning (Curcubita Moschata) dan Penambahan Chia Seed (Salvia Hispanica) terhadap Daya Terima dan Kandungan Gizi Cookies sebagai Alternatif Selingan untuk Obesitas pada Usia Dewasa Muda - Anisah Qurrotu Ayun; Veni Indrawati (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Cookies are one type of biscuit made from soft dough, relatively crispy, and the appearance of the pieces has a solid texture that is in great demand by all groups. Cookies with pumpkin flour substitution and the addition of chias seed contain fiber and antioxidants that serve to reduce risk factors for obesity. The study aims to analyze the effect of yellow pumpkin flour subtitration and the addition of chia seeds on the receptivity and nutritional content of cookies as an alternative counterpart to young adult obesity. This type of research is pure experimental research using a 3x2 factorial design. Data collection was done by observation through hedonic test of level of liking (color, aroma, texture, and taste) by 36 untrained panelists using an observation sheet. Data analysis in this study used the SPSS multiple variance analysis method (Two Way ANOVA) and Duncan's further test. After determining the best product, nutritional content tests were conducted at the Surabaya Nutrition Laboratory to determine fiber and antioxidant content. The results showed that: 1) Substitution of pumpkin flour affects the color of cookies but has no effect on aroma, texture and taste; 2) Addition of chia seed has no effect on the color, aroma, texture and taste of cookies; 3) The interaction of pumpkin flour substitution and chia seed addition has no effect on the color, aroma, texture, and taste of cookies. 4) The nutritional content of the best favorability test results in formula L2C2 (30% pumpkin flour substitution and the addition of chia seed as much as 10%) per 100 grams of cookies is obtained with a fat content of 13.1 grams, fiber 7.71 grams, and antioxidants 26 mg with recommended consumption of cookies at serving of 49 grams or 7 pieces containing 6.4 grams of fat, 3.8 grams of fiber and 12.7 mg of antioxidants. The conclusion of this study is that the subtitration of yellow pumpkin flour affects the color of cookies but does not affect the aroma, texture and flavor; the addition of chia seeds does not influence the color, aroma, texture and flavour of cookies; the interaction of subtitrating yellow pummel flour and adding chia seed has no effect on the colour, flavours, textures, and flavors in cookies; as well as the nutritional content of the best liking test results on formula L2C2 (subtitrations of 30% yellow pasta and additions of 10% Chia seed).